Smallholder Agriculture Commercialization in Rwanda, 2022 - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
This dataset pertains to a survey on smallholder commercialization conducted in Rwanda during October and November of 2022. The primary objective of this study is to enhance data and analysis regarding the returns associated with commercial smallholder production systems and policies aimed at supporting smallholder commercialization.